FACTORS CONTRIBUTING TO DISPENSING ERRORS AMONG HEALTH WORKERS AT KAWOLO HOSPITAL, BUIKWE DISTRICT. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - NAMUTEBI, HASHURAH; Oketcho , Stephen (Student's Journal of Health Research Africa, 2023)
Background. The specific objectives of the study were to determine the; individual factors, health facility-related factors, and medicines-related factors contributing to dispensing errors among health workers. Methodology. A descriptive cross-sectional study design was used to address the relationship between the study variables from 50 respondents with a simple random technique to select the study participants. Results. 56% had ever experienced preventable dispensing errors, 75% didn’t report it, 54% got tempted to be distracted at work, 66% said the quality of prescription writing of fellow workmates was fair, 72% were satisfied with their jobs, 68% noted that their fellow workmates are friendly and 50% had fair computer skills. 52% didn’t have enough dispensers as per the ratio of patients,92% reported that the condition of their working environment was organized, 58% reported that sometimes workmates from different departments accessed the dispensing unit, 70% reported that medicines were assembled on shelves according to pharmaceutical therapeutic order, 60% never had enough space between medicines on shelves in their dispensing units, 90% agreed that the facility had policies related to dispensing. 58% agreed that they had ever experienced drug strength confusion during dispensing, 59% reported endocrine system agents as the classes of medicines they had ever experienced drug strength confusion during dispensing, 78% had never dispensed expired medicines accidentally, 48% had fair labelling strength for medicines, 54% agreed that the packaging of the medicine was decent. Conclusion. Poor reporting systems, distraction at work, quality of handwriting skills, unauthorized access to dispensing units, the inadequacy of dispensers as per the ratio of patients, lack of enough space, and drug strength confusion were factors contributing to dispensing errors among health workers. Recommendations. The administration should minimize the work overload, limit unauthorized access to dispensing units, and enforce protocol for patient identification and verification of drugs dispensed.